How Ca + HNO3 => Ca (NO3) 2 + N2O + H2O ?
Can anyone explain me how to get this?
4Ca + 10HNO3 = 4Ca (NO3) 2 + N2O + 5H2O
- Roger the MoleLv 77 years agoFavorite Answer
Ca + HNO3 → Ca(NO3)2 + N2O + H2O
The only practical way I see is to use simultaneous equations.
Start by assigning algebraic variables to each species:
a Ca + b HNO3 → c Ca(NO3)2 + d N2O + e H2O
Write a balanced equation for each element:
Ca: a = c
H: b = 2e
N: b = 2c + 2d
O: 3b = 6c + d + e
Solve these four equations simultaneously in terms of a, using whatever algebraic method you prefer:
a = a and b = (5a)/2 and c = a and d = a/4 and e = (5a)/4
Substitute these values in a into the original equation:
a Ca + (5a)/2 HNO3 → a Ca(NO3)2 + a/4 N2O + (5a)/4 H2O
Multiply each coefficient by 4/a to eliminate the fractions and the single remaining variable a:
4 Ca + 10 HNO3 → 4 Ca(NO3)2 + N2O + 5 H2O